2011
DOI: 10.1103/physrevc.84.037301
|View full text |Cite
|
Sign up to set email alerts
|

Coupled-channels study of fine structure in theαdecay of platinum isotopes

Abstract: The fine structure observed in the α decay of deformed platinum isotopes is investigated using the recently developed five-channel formalism, based on the coupled-channel Schrödinger equation with outgoing wave boundary conditions. The internal effect of daughter states is taken into account in dealing with the interaction matrix and the α-cluster formation. The available experimental data concerning α-decay half-lives and fine structures are reproduced. Some predictions are made especially for the α decay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Among these, various models incorporating parent and daughter ground-state (GS) deformations are developed, such as the unified model for α decay and α capture [8], generalized density-dependent cluster model [9], and Coulomb and proximity potential model for deformed nuclei [10,11], which show the reduction of barrier height due to quadrupole deformation. In fact, in the case of a deformed parent, there are a lot of accessible ground states and low-lying excited states in the daughter nucleus [8,9], so there is the possibility of coupling of these states during tunneling process through the potential barrier, and a realistic coupled channel treatment can be used to address these effects [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, various models incorporating parent and daughter ground-state (GS) deformations are developed, such as the unified model for α decay and α capture [8], generalized density-dependent cluster model [9], and Coulomb and proximity potential model for deformed nuclei [10,11], which show the reduction of barrier height due to quadrupole deformation. In fact, in the case of a deformed parent, there are a lot of accessible ground states and low-lying excited states in the daughter nucleus [8,9], so there is the possibility of coupling of these states during tunneling process through the potential barrier, and a realistic coupled channel treatment can be used to address these effects [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…16), 17). The previous systematic calculations of 35 deformed α emitters 17) have shown that the experimental branching ratios to various states and total α-decay half-lives can be well reproduced with the same factor P α = 0.36 and the same BD c = 2.38 MeV −1 . §3.…”
Section: Nuclear Structure Part Of α Decaymentioning
confidence: 88%
“…18) The Q α formula for superheavy nuclei was proposed by Dong and Ren, 19) where the macroscopic terms are based on the well-known Weizsäcker-Bethe mass formula and the shell corrections are simulated by the Mexican hat wavelet functions. Additionally, the predictive power of the MCCM has been checked for a wide range of deformed α emitters including the newly measured neutron-rich Pt isotopes, 17) where the five-channels microscopic calculations well reproduced the available experimental data concerning α-decay half-lives and fine structures. Encouraged by these successes, in this work we intend to perform a detailed study of the fine structure in the α decay of Rf to Hs isotopes within the MCCM.…”
Section: §1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Gamow wrote a closed formula between the logarithmic values of half-lives and the Q-values, this relation and formula were also obtained by Geiger and Nuttall [6]. In recent years studies considering deformations on the α -decay of heavy and super heavy nuclei have become interesting and popular research avenues [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%